An Arabidopsis downy mildew non-RxLR effector suppresses induced plant cell death to promote biotroph infection. (16th October 2020) - Dunker, Florian; Oberkofler, Lorenz; Lederer, Bernhard; Trutzenberg, Adriana; Weiberg, Arne
Abstract: Our understanding of obligate biotrophic pathogens is limited by lack of knowledge concerning the molecular function of virulence factors. We established Arabidopsis host-induced gene silencing (HIGS) to explore gene functions of Hyaloperonospora arabidopsidis, including CYSTEINE-RICH PROTEIN ( HaCR ) 1, a potential secreted effector gene of this obligate biotrophic pathogen. Ha CR1 HIGS resulted in H. arabidopsidis -induced local plant cell death and reduced pathogen reproduction. We functionally characterized Ha CR1 by ectopic expression in Nicotiana benthamiana . Ha CR1 was capable of inhibiting effector-triggered plant cell death. Consistent with this, Ha CR1 expression in N. benthamiana led to stronger disease symptoms caused by the hemibiotrophic oomycete pathogen Phytophthora capsici, but reduced disease symptoms caused by the necrotrophic fungal pathogen Botrytis cinerea . Expressing Ha CR1 in transgenic Arabidopsis confirmed higher susceptibility to H. arabidopsidis and to the bacterial hemibiotrophic pathogen Pseudomonas syringae . Increased H. arabidopsidis infection was in accordance with reduced PATHOGENESIS RELATED ( PR ) 1 induction. Expression of full-length Ha CR1 was required for its function, which was lost if the signal peptide was deleted, suggesting its site of action in the plant apoplast. This study provides phytopathological and molecular evidence for the importance of this widespread, but largely unexplored class of non-RxLR effectors in biotrophic oomycetes. Abstract : Induced cell death is a crucial component of plant defence. An extracellular downy mildew cysteine-rich protein effector inhibited plant cell death enabling host colonization.